PROSPECT TO ACHIEVING EQUITABLE URBAN TREE CANOPY DISTRIBUTION IN IBADAN METROPOLIS, OYO STATE, NIGERIA - Fasoro, Oyinlola; Salam, Sofiyat (Polish Journal of Natural Sciences, 2025)
Oluyole’s vegetation cover rose from 0.08 in 2003 to 0.36 in 2013, but declined to 0.32 in 2023, whereas Old Bodija’s increased from 0.11 in 2003 to 0.39 in 2013, but decreased to 0.35 by 2023. In Oluyole and Old Bodija, 55.2% and 54.7% of respondents were males, 55.2% and 62.3% were 20 to 35 years old, and 58.3% and 49.1% earned more than ₦40,000(27) monthly. Yoruba(78.5% and 75.5% respectively) were the majority ethnic group in both areas, with 70.6% and 75.5% renting their homes. Oluyole residents(74.8%) believed vegetation cover is unequally distributed, despite equal access (59.5%). Old Bodija residents(69.8%) claimed vegetation cover is evenly distributed and that there is equitable access. Chi-square(χ2) indicated that gender(0.041), age(0.002), and education(0.024) significantly influence canopy cover’s distribution. Pursuit of equitable urban tree distribution is an important step in building sustainable, resilient, and equitable communities; hence policymakers should prioritize equity in urban climate policies.